Institutions and individual values motivating corporate social responsibility activities in large farms and agroholdings - Hajdu, Anna (2021)
Fil: Hajdu, Anna. Institute of Agricultural Development in Transition Economies (IAMO). Department Change. Halle. (Saale), Germany.